THE INFLUENCE OF SATISFACTION ON CONSUMER LOYALTY OF SUMAWE COFFEE MALANG - Yulita Anggraeni; Dwi Retnoningsih; Abdul Wahib Muhaimin (Agricultural Socio-Economics Journal, 2019)
Abstract: The most famous coffee in Malang Regency is Amstirdam coffee and one of them is Sumawe coffee. Sumawe coffee is a robusta coffee from Sumbermanjing Wetan Sub District but not widely known yet. However this coffee has the potential of coffee to be improved to satisfy consumers. Producers who are able to satisfy consumers and have loyal consumers tend to survive in the competition. The purpose of this research is analyzing the influence of satisfaction on consumer loyalty Sumawe coffee. The sampling data was gathered from consumers Sumawe coffee with the number of sample is 40 respondents. The data are analyzed by using a Structural Equation Modeling Partial Least Square (SEM-PLS) technique. The results of analysis showed that product quality and price perception have a positive and significant influence on consumer satisfaction. Consumer satisfaction has a positive and significant influence on consumer loyalty. Product quality and price perception also have a positive and significant influence on consumer loyalty.